The National Element in Polish Music of the Period of the Partitions – Symbolic Violence or Weaponised Culture? - Poniatowska, Irena (Interdisciplinary Studies in Musicology, 2023)
This study presents the concept of nationality in Polish music during the partition period as an interaction of three basic conceptual categories and evolution of their perception. The first one is a modern concept of nation, covering all social strata, being formed since the beginning of the 19th century and developed in the period between the November and January Uprisings. Historians apply the concepts of Johann Georg Herder and Stanisław Staszic unifying the role of a language. The second category is Romanticism as an aesthetic and social challenge that underlines personality and subjectivity rather than ethnic or social origins; as a concept of deepest spirituality expressed in non-conceptual art of music. All the elements making up the concept of nationality drew their strength from the third category – historicism which took control over the culture and art of the century. Almost mythical vision of an ideal, historic homeland dominated music, to the highest degree the operas on Polish themes, and, on unprecedented scale, adaptations of the canon of the greatest Polish literature (Słowacki, Mickiewicz, Kraszewski, Sienkiewicz, Wyspiański). In spite of the emergence of Positivism, the Romantic motifs in Polish poetry and belletristic such as the need for sacrifice to save Poland did not vanish. Similarly, in the fine arts, especially in the 2nd half of the 19th century, a remarkable growth in historic painting was observed. ‘Not only a sword but also a book promised salvation’, writes Alina Witkowska.